Risk factors, clinical characteristics and outcome in neonates with meconium aspiration syndrome - an experience at tertiary care hospital - Chesti, Mohmad S.; Shahzad, Naveed; Goswami, Shivani; Gazala, Sheenam (International Journal of Contemporary Pediatrics, 2022)
Background: Meconium aspiration syndrome (MAS) is a life-threatening condition involving respiratory system, the present study was undertaken to study maternal risk factors associated with MAS, etiology, incidence of MAS born via meconium-stained amniotic fluid (MSAF) and to assess outcome of neonates born with MAS. Methods: The present study was carried out at Government Medical College, Baramulla from August 2017 to August 2019, all neonates fulfilling inclusion criteria got admitted in neonatal intensive care unit (NICU) and were included in our study after obtaining informed consent from their parents. The demographic and factors related to MAS were recorded through predesigned proforma and analyzed using Microsoft excel. Mean and standard deviation were determined for quantitative variables whereas frequency and percentages were calculated for qualitative variables. Results: Newborn with MAS were mostly depressed at birth and hypoxic ischemic encephalopathy (HIE stage III) was main cause of neonatal mortality, significantly contributing 37.5% of cases of MAS. Neonatal mortality in MAS was also associated with 5 minute low APGAR score. There was significant and strong association between the birth weight and mortality. Thick MSAF was significantly associated with need for mechanical ventilation and subsequently higher mortality. Conclusions: We conclude from our study that MAS is most commonly seen in term and post term babies with birth weight >2.5 kg. Risk factors should be identified and timely intervention should be done to reduce, mortality and morbidity in MAS.